Effect of Magnetic field on the growth of Escherichia coli and Staphylococcus aureus - Samir H.Nasher; Amal A.Hussein (Engineering and Technology Journal, 2008)
Magnetic fields with two densities (1200 , 3200)gauss experminted on twokinds of bacteria Escherichia coli and Staphylococcus aureus in Nutrient brothmedia . The field subjected for (1,2,3) weeks, and the growth monitored usingoptical density (OD) method.The results shows greatest effects of 3200 gauss than 1200 gauss on bacteriagrowth comparing with control sample after third week. The OD resulte of bacteriaEscherichia coli (0.3) with 3200 gauss and (6) with 1200 gauss comparing withcontrol sample(175.4) and bacteria Staphylococcus aureus (1) with 3200 gauss,and (10) with 1200 gauss comparing with control sample (174.4).